STRUCTURAL FEATURES AND SEMANTIC NATURE OF COMPARISONS IN THE LINGUISTIC CANVAS OF THE NOVELS BY MARK CHEREMSHYNA - Bihusiak, Mykhailo (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
The article describes the structural features and semantic space of comparative compounds in the fictional language of Marko Cheremshyna, which he uses quite often among other tropes. The study is based on the material of the author’s card index of comparisons, which includes more than 600 units used by the author in 35 short stories published in the academic two-volume collection of his works. According to our observations, the writer can use up to twenty comparative phrases in one short story. In the linguistic canvas of the short stories, conjunctive comparisons prevail. The specifics of the conjunctions that connect the comparative component, as well as the conjunctionless constructions expressed by the form of operative comparison and comparative conjunctions are described. Attention is paid to extended comparisons, their semantic features, which, based on various features of the object of comparison, evoke a wide range of associations and analogies in the reader’s imagination. It is noted that the semantic nature of similes in the language of the author’s short stories is multifaceted. Most of the subjects of comparisons are in the semantic field of a person. With the help of such compounds, the author describes the appearance of a person, presents a linguistic portrait of his characters. All this contributes to the creation of colourful visual images. Based on the studied materials, six lexical and semantic groups have been identified among the objects of comparison, which contain words that concentrate the main figurative and expressive content of the comparison: names of birds, flora and fauna, natural phenomena, everyday realities, substances and food. Along with this, in the artistic language of the short stories, we observe the frequent use of traditional and individually-authored comparatives that are marked by freshness and unusualness, along with many specific Hutsul expressions that enhance the reader’s imagination. It is concluded that comparative phrases are the dominant idiom of the novelist’s idiom. They are marked by figurative and semantic complexity, novelty and originality. Aesthetically complicating the artistic image, comparisons ensure its integrity, expressiveness and expressiveness.